Development of Learning Media for PEN Material (Puzzle Nusantara) Cultural Diversity to Improve Learning Outcomes of Fourth Grade Students at MIS Al-Falah Lemahabang - Yusril Wahid; Nuril Nuzulia; Moch. Bahak Udin By Arifin (Madrosatuna: Journal of Islamic Elementary School, 2020)
The Development of PENA (Puzzle Nusantara) Learning Media on Cultural Diversity Material is one of the instruments to help students understand the diversity material to increase learning outcomes in Indonesian cultural diversity material. The necessity to provide attractive and creative learning media in learning that aims to increase student learning outcomes is one of the reasons behind this research and development. The purpose of this research and development are to (1) determine the process in the making of PENA (Puzzle Nusantara) learning media on cultural diversity material to increase learning outcomes of fourth grade student MIS Al-Falah Lemahabang, (2) knowing the attractiveness level of PENA learning media (Puzzle Nusantara) on cultural diversity material in improving the learning outcomes of fourth grade student MIS Al-Falah Lemahabang, (3) knowing is there any differences in learning outcomes of fourth grade student before using PENA (Puzzle Nusantara) learning media and after using PENA (Puzzle Nusantara) learning media. This research and development method uses research and development (R&D) research type. This research development procedure uses the Borg and Gall model by adopting six stages including (1) research and data collection, (2) planning, (3) product development, (4) preliminary product testing, (5) after product testing revisions, (6) field trials. This research was conducted at MIS Al-Falah Lemahabang, Bone-Bone, North-Luwu, South Sulawesi. Data collection techniques in this study were tests and observations. The data obtained were analyzed descriptively and qualitatively. The result of this conducted development is in the form of printed learning media called PENA (Puzzle Nusantara) with Indonesia cultural diversity material. (1) the results of this research and development meet the valid criteria with the acquisition of validity, material expert gets 97.5%, design expert gets 95.45%, and learning expert gets 95%. (2) the test results to rate the attractiveness of the PENA (Puzzle Nusantara) learning media (Puzzle Nusantara) in fourth grade students at MIS Al-Falah Lemahabang by 95.5%. (3) student learning outcomes increased, proved by the pre-test results of 46.5, and the post-test scores of 81, it can be said that the PENA (Puzzle Nusantara) learning media is feasible for students.